Transformasi Limbah Kulit Singkong Sebagai Bahan Alternatif Mie pada Program PELITA SIMIE Mahasiswa KKN Kolaboratif untuk Pemberdayaan Ekonomi Desa Jubung - Hadi, Bimoseno Prasteyo; Mufidah, Salma Fitria; Nisak, Chonitatun; Sabilillah, Zico; Vembriani, Hanifah Fariuz; Sari, Devi Novita; Wijaya, Daniel Aries; Mahardika, Sherly; Hernawan, Salsabiela; Nastiari, Samara Galih Dhiya; Humaimah, Calista Nurifa; Rahayu, Muji; Qomariyah, Siti; Sukoco, Sampir Andrean (Abdimas Indonesian Journal, 2025)
The Collaborative Community Service Program (KKN) 159 conducted in Jubung Village, Sukorambi Subdistrict, Jember Regency, is a tangible contribution by students to community service, focusing on processing cassava peel waste into an alternative raw material for noodles through the PELITA SIMIE Program (Empowerment Through Appropriate Innovation: Cassava Peel into Noodles). Activities included waste collection, processing, and training in noodle production for the community, particularly small and medium enterprises (SMEs), using efficient and environmentally friendly techniques. As a result, cassava peel waste was successfully processed into high-quality noodles, increasing residents' income and fostering awareness of waste management and local product innovation. This initiative has the potential to serve as a model for sustainable economic empowerment based on local resources.